Air stimulation in tympanic perforation: inverted nystagmus study - Nishino,Lucia Kazuko (2009)
Response inversion during warm air stimulation is the most controversial finding seen in caloric tests of individuals with tympanic membrane perforation. In such cases, very few studies explore the possible interferences found in the caloric test, bringing about controversies in the interpretation of test results. AIM: This paper aimed at analyzing warm air stimulation effects in individuals with tympanic membrane perforation in comparison with normal healthy controls. MATERIALS AND METHODS: Prospective, non-randomized study in which 48 individuals without vestibular complaints were assessed, 33 had one tympanic membrane perforated and 15 had no ear drum alteration. RESULTS: 39.39% of the individuals had response inversion found during the warm air test. In the absence of this phenomenon, nystagmus responses were symmetrical. CONCLUSION: Nystagmus responses to the caloric test in individuals with tympanic membrane perforation were similar to those from healthy controls, with the exception of the fact that they had inverted responses in the warm caloric test.